2022
DOI: 10.3390/ijms23031743
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Fiber-Coated Human Amniotic Membrane: A Potential Angioinductive Scaffold for Ischemic Tissue Repair

Abstract: Cardiac patch implantation helps maximize the paracrine function of grafted cells and serves as a reservoir of soluble proangiogenic factors required for the neovascularization of infarcted hearts. We have previously fabricated a cardiac patch, EF-HAM, composed of a human amniotic membrane (HAM) coated with aligned PLGA electrospun fibers (EF). In this study, we aimed to evaluate the biocompatibility and angiogenic effects of EF-HAM scaffolds with varying fiber thicknesses on the paracrine behavior of skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Then, the cell culture inserts were incubated in the dark with 1ml 4′,6-diamidino-2-phenylindole (DAPI; Thermo Fisher Scientific, Carlsbad, CA, USA) at 1:15,000 dilution for each well for 40 min at room temperature, and then were washed thrice with PBS. Pictures of DAPI-stained nuclei at the bottom of the inserts were taken at five different fields using an immunofluorescence microscope (Nikon, Tokyo, Japan) before the numbers of nuclei were averaged [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, the cell culture inserts were incubated in the dark with 1ml 4′,6-diamidino-2-phenylindole (DAPI; Thermo Fisher Scientific, Carlsbad, CA, USA) at 1:15,000 dilution for each well for 40 min at room temperature, and then were washed thrice with PBS. Pictures of DAPI-stained nuclei at the bottom of the inserts were taken at five different fields using an immunofluorescence microscope (Nikon, Tokyo, Japan) before the numbers of nuclei were averaged [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Both synthetic and natural polymers were used as secondary materials to create electrospun multilayered composite AM (Table 1). The synthetic electrospun polymers were polycaprolactone (PCL) [74,84,86,88,89,[97][98][99], poly(lactic-co-glycolic acid) (PLGA) [90,91,97], poly(lactic acid) (PLA) [97], and poly-(Llactide-co-E-caprolactone) (PCLC) [85]. They were all biodegradable and biocompatible synthetic polymers.…”
Section: Electrospun Multilayered Composite Amniotic Membrane and Sec...mentioning
confidence: 99%
“…They also reported that skeletal muscle cells seeded on AM-PLGA scaffolds were oriented along the alignment of the electrospun PLGA fibers, whereas cells seeded on AM displayed random orientation, thereby guiding the orientation and migration of skeletal muscle cells owing to their aligned topography. In a further study, they investigated the proangiogenic potential of the same skeletal muscle cell-seeded composite scaffolds according to three different thicknesses of PLGA fibers [91]. Thus, they compared in vitro the angiogenic paracrine effects of (i) these three skeletal muscle cell-seeded composite scaffolds, (ii) skeletal muscle cellseeded AM, and (iii) non-seeded skeletal muscle cells on human umbilical vein endothelial cells (HUVECs).…”
Section: In Vitro and In Vivo Assessment Of Electrospun Multilayered ...mentioning
confidence: 99%